Raising Environmental Awareness in Kampong Tridi and Kampong Warna-Warni (Malang, Indonesia) through Digital-Based Workshop on Constructed Wetlands - Anie Yulistyorini; Harits Ar Rosyid; Diederik Rousseau; Mohammad Musthofa Al Ansyorie; Kusuma Refa Haratama (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Kampong Tridi and Warna-Warni are two small communities in Malang, Indonesia, which have started efforts to realize a sustainable environment within a broader national movement to eliminate slum areas. Colourful artwork and painted murals have made them popular tourist spots that attract 150 tourists per day on average, which helps boost the local economy. However, both kampongs are still lacking sanitation service. Blackwater and greywater generated from inhabitants’ activities are directly dumped into the Brantas River, negatively impacting water quality. A workshop was organized to increase the participants’ awareness of environmental issues, particularly in water resource sustainability, and obtain a commitment to adopt constructed wetlands as sustainable, nature-based solutions for wastewater treatment. Two types of the questionnaire (pretest and posttest) were distributed to 50 participants to identify perception differences generated through the workshop. A digital game and a 3D simulation were developed to educate the participants on constructed wetlands as wastewater treatment systems in fun, attractive, and effective ways. Participants’ awareness of environmental issues in water resources increased from 67% to 76%, and the workshop had motivated the participants to adopt constructed wetlands in their neighbourhood.